The rotifera fauna of the Bayezid Bostami pond of Chittagong city - Akter, Sajeda; Bhouyain, Abdul Maleque (Bangladesh Journal of Zoology, 2015)
Rotifera fauna of Bayezid Bostami pond was studied for a period of one year from February 2013 to January 2014. Brachionus diversicornis, B. angularis, B. quadridentatus, B. falcatus, B. calyciflorus, B. forficula, B. caudatus, Platyias patulus, Keratella cochlearis, Lecane luna, Trichocerca cylindrica, Polyarthra vulgaris, Asplanchna priodonta, A. brightwelli, Filinia longiseta and F. terminalis were common species present throughout the year. Highest abundance of rotifer was observed in the month of September, and lowest was observed in the month of March. The responsible species for the peak were Brachionus angularis and B. diversicornis. Description of each species, monthly fluctuation and photographs are the content of this paper. Bangladesh J. Zool. 43(1): 95-108, 2015